2020
DOI: 10.1021/jacs.9b11126
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Oxidation State of the Cu Electrode and Reaction Intermediates for Electrochemical CO2 Reduction to Ethylene

Abstract: Understanding the role of oxidation state of Cu surface and surface-adsorbed intermediate species in electrochemical CO2 reduction is crucial for the development of selective CO2-to-fuel electrocatalysts. In this study, the electrochemical CO2 reduction mechanism over the Cu catalysts with various oxidation states was studied by using in situ surface-enhanced infrared absorption spectroscopy (SEIRAS), in situ soft X-ray absorption spectroscopy (Cu L-edge) and on-line gas chromatography measurements. The atop-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
281
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 433 publications
(303 citation statements)
references
References 58 publications
21
281
1
Order By: Relevance
“…Although the Cu LMM Auger peak indicates that the surface of nano powder has been oxidized, numerous studies [40][41][42][43][44] indicate that such a naturally formed oxide shell can be quickly reduced under working condition. Despite the ongoing debate in the community towards the existence and function of oxygen residue during CO2RR [45][46][47] , we note that such a phenomenon will not influence the conclusions related to tandem interactions between Ag and Cu of the later discussion in this work. Meanwhile, it is widely reported that Cu can undergo surface reconstruction and structural evolution during CO2 electrolysis, [48][49][50][51] and previous reports have also invoked Cu-Ag alloy [13][14][15] or surface alloy 16 strategies to im-To further probe the role of local CO towards the C2+ enhancement, the net CO producing abilities over these catalysts are also compared (Fig.…”
Section: Electrode Characterizationmentioning
confidence: 85%
“…Although the Cu LMM Auger peak indicates that the surface of nano powder has been oxidized, numerous studies [40][41][42][43][44] indicate that such a naturally formed oxide shell can be quickly reduced under working condition. Despite the ongoing debate in the community towards the existence and function of oxygen residue during CO2RR [45][46][47] , we note that such a phenomenon will not influence the conclusions related to tandem interactions between Ag and Cu of the later discussion in this work. Meanwhile, it is widely reported that Cu can undergo surface reconstruction and structural evolution during CO2 electrolysis, [48][49][50][51] and previous reports have also invoked Cu-Ag alloy [13][14][15] or surface alloy 16 strategies to im-To further probe the role of local CO towards the C2+ enhancement, the net CO producing abilities over these catalysts are also compared (Fig.…”
Section: Electrode Characterizationmentioning
confidence: 85%
“…These surface sulfur atoms can be removed to form sulfur vacancies, designated as CuS x (0 < x < 1) 31 , 33 . The controlled sulfur vacancies can lower the oxidation of copper between 0 and +2, which has been proved to promote C–C coupling 34 . Herein, we developed a double-sulfur vacancy (DSV) structure using a lithium electrochemical tuning approach, which allowed for stabilization of both CO* and a *C 2 dimer (i.e., OCCO*), as well as subsequent coupling with a third *CO via CO–OCCO (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In recent several years, Cu has attracted wide research interests, as it is the overriding inexpensive transition metal and can be capable of producing valuable multicarbon products. [ 8,10,37–39 ] In this work, Cu dimer anchored in g‐CN (Cu 2 @CN) monolayer as a promising CO 2 RR electrocatalyst is investigated and discussed in detail using density functional theory (DFT) calculations. Our computational results show that the Cu 2 @CN monolayer can electrochemically convert CO 2 to various hydrocarbons, including HCOOH and C 2 H 4 , whose excellent catalytic performance exceeds that of the corresponding single‐atom counterpart (Cu@CN).…”
Section: Introductionmentioning
confidence: 99%